ANALISIS KINERJA ZAKAT DENGAN MENGGUNAKAN INDEKS ZAKAT NASIONAL PADA BADAN AMIL ZAKAT NASIONAL - Usamah, Usamah; Moegiri, Moegiri (Unitri Press, 2023)
This research aims to measure the achievement of zakat management activities andprovide an overview of the extent of the role of the government and society or referred to asthe macro dimension as well as in the institutional perspective of zakat as well as the impactof zakat on mustahik which is included in the micro dimension, The approach used isquantitative and the methode of the National Zakat Index (IZN) as an instrument formeasuring the performance of zakat management at the Pekalongan City Baznas., Result anddiscussions: Based on the calculation results of BAZNAS Pekalongan City Permit on themacro dimension is worth in the range 0.00 – 1.00 where this index is in the good categoryand on the micro dimension is worth 0.75 this index is in the good category. So that theresults of the Aggregate BAZNAS score for Pekalongan City are 0.516., The results of thisstudy are in accordance with previous research conducted by Hidayaneu (2017) at theBandung City BAZNAS, Nadhia (2017) at the South Jakarta City BAZIS, Yunita (2017) at theYogyakarta City BAZNAS, Ulfah (2017) at the Bogor Regency BAZNAS. Conclusion: Thatvalue above illustrates the performance achievement of Pekalongan City BAZNAS zakatmanagement in the Fairly Good category the result report and the information about thefindings